2015
DOI: 10.1007/s00415-015-7648-0
|View full text |Cite
|
Sign up to set email alerts
|

Nerve ultrasound for differentiation between amyotrophic lateral sclerosis and multifocal motor neuropathy

Abstract: Ultrasound is useful for non-invasive visualization of focal nerve pathologies probably resulting from demyelination, remyelination, edema or inflammation. In patients with progressive muscle weakness, differentiation between multifocal motor neuropathy (MMN) and amyotrophic lateral sclerosis (ALS) is essential regarding therapy and prognosis. Therefore, the objective of this study was to investigate whether nerve ultrasound can differentiate between ALS and MMN. Systematic ultrasound measurements of periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 43 publications
9
102
6
6
Order By: Relevance
“…This finding was confirmed by a recent report employing high resolution sonography in MMN patients (3,15,16), but its utility for differential diagnosis, especially in MMN patients without solid diagnostic evidence (e.g., CB and/or anti-ganglioside antibodies), had been little explored. We have thus demonstrated that, in patients with otherwise typical MMN but no overt CB, sonography can provide evidence of demyelination.…”
Section: Discussionsupporting
confidence: 68%
“…This finding was confirmed by a recent report employing high resolution sonography in MMN patients (3,15,16), but its utility for differential diagnosis, especially in MMN patients without solid diagnostic evidence (e.g., CB and/or anti-ganglioside antibodies), had been little explored. We have thus demonstrated that, in patients with otherwise typical MMN but no overt CB, sonography can provide evidence of demyelination.…”
Section: Discussionsupporting
confidence: 68%
“…MRI [24, 25], and more frequently, peripheral nerve ultrasound [26, 27] is used to ascertain the diagnosis of immune-mediated neuropathies. In our series, however, such imaging studies have not been applied in a systematic matter and no conclusions regarding imaging can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in MMN, ultrasonography can detect enlargement of nerves at sites that are not clinically involved 94 , although the enlargement in cross-sectional area has a weak correlation with electrophysiological findings 95 . Nevertheless, ultra sonography might help to differentiate MMN from lower motor neuron disease 96,97 , as enlarged nerves or roots are more common in MMN.…”
Section: Notalgiamentioning
confidence: 99%